Stimulating mathematical communication with SPECOMATSO technology development based on digital literacy - Andriyani Andriyani; Meita Fitrianawati; Ibrahim Alhussain Khalil; Muya Barida; Rully Charitas Indra Prahmana (Universitas Hamzanwadi, 2023)
Mathematical communication is crucial in inclusive mathematics teaching and learning to convey mathematical symbols. However, teaching mathematical symbols to deaf students in inclusive classrooms has been a persistent challenge due to the lack of specialized sign language for mathematical expressions. Media, such as SPECOMATSO technology, can serve as a bridge to address this issue. This research focused on developing valid and practical SPECOMATSO technology to strengthen students’ literacy and facilitate the delivery of mathematical symbols, which previously posed difficulties for teachers in inclusive settings. The research combined the Alessi & Trollip and V-waterfall models, encompassing seven development stages: analysis, design, implementation, unit testing, integration testing, system testing, and acceptance testing. The research instruments included observation and interview guidelines, a product validation questionnaire, and a student response questionnaire. This study produces SPECOMATSO technology that is valid and practical for learning plane geometry and angles in mathematics. Although this development still needs improvement in fixative abilities, such as storage and editing functions, it is expected to strengthen digital literacy and stimulate mathematical communication among deaf students who face challenges related to their limited auditory capabilities.